2019
DOI: 10.5603/ep.a2019.0005
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly associated with GIST, non-small cell lung carcinoma, clear cell renal carcinoma, multiple myeloma, medulla oblongata tumour, adrenal adenoma, and follicular thyroid nodules

Abstract: Acromegaly is associated with increased growth hormone (GH) and insulin-like growth factor-I (IGF-I) secretion which may support tumour development and growth. A 68-year-old woman was diagnosed with acromegaly due to typical clinical and hormonal characteristics. While contrast-enhanced MRI at diagnosis did not reveal a pituitary adenoma, a 5-mm lesion was identified on repeat scanning 13 months later. Abdominal and chest CT showed tumours of the stomach, right adrenal gland, and right lung. The CT also showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Subjects with acromegaly, which is due to excessive GH secretion, have elevated levels of serum IGF-1 and are well-recognized to be at increased risk of colorectal cancer, with possible association also with breast, thyroid and prostate cancers and a recent report of multiple additional tumors including cancers of the lung, kidney, adrenal and GIST [74,75]. There are additional health risks associated with chronic exposure to high circulating IGF-1, including increasing bone fragility.…”
Section: Disease States Characterized By Igf Axis Activationmentioning
confidence: 99%
“…Subjects with acromegaly, which is due to excessive GH secretion, have elevated levels of serum IGF-1 and are well-recognized to be at increased risk of colorectal cancer, with possible association also with breast, thyroid and prostate cancers and a recent report of multiple additional tumors including cancers of the lung, kidney, adrenal and GIST [74,75]. There are additional health risks associated with chronic exposure to high circulating IGF-1, including increasing bone fragility.…”
Section: Disease States Characterized By Igf Axis Activationmentioning
confidence: 99%
“…However, there are patients in the literature in whom multiple cancers coexist that have been presented as case reports. In a case report presented by Aleksandra et al, although no genetic predisposition was found, GIST, non-small cell lung carcinoma, clear cell renal carcinoma, multiple myeloma, medulla oblongata tumor, adrenal adenoma, and follicular thyroid nodules were detected in the same patient 23 . In a case report presented in 1997, four types of tumors were found in the same patient: gastric cancer, colon tubular adenoma with moderate atypia, pancreatic mucinous cystadenoma, and subcutaneous lipoma 24 .…”
Section: Discussionmentioning
confidence: 80%
“…По литературным данным, на сегодняшний день всего в мире описаны 8 случаев сочетания ММ и рака легкого [9][10][11][12][13][14][15]. Соотношение женщин к мужчинам -3:5.…”
Section: Discussionunclassified